The treasury of David ; v. 2 a commentary on the Psalms in seven volumes - Spurgeon, Charles Haddon, 1834-1892 (London, UK Hodder and Stoughton, 1905)
Includes bibliographical references and index. Contents : v. 2 : Psalms 27-52.
Keywords: Bible. O.T. Psalms XXVII-LII -- commentaries